Modelos mecânicos para o estudo da dinâmica do DNA - Slade, Gabriel Gouvêa [UNESP] (2013)
The dynamic behavior of the DNA shows motions of great amplitude and localized by the chain. The motions are even capable to open a single base pair on its biological temperature. This behavior is related to functional aspects of the molecule, like transcription and replication. In this work, we aim to understand this dynamic through the creation of breathers and its stability in the Peyrard-Bishop model. We study the in uence of the energy change in a stable breather solution. By the dynamic of the model, we infer the energy density that is needed to happen the phase transition in the system, that is, the DNA denaturation in a minimalistic view. In the sequence, we use atomistic molecular dynamics to relate the mechanical model with the in silico dynamic of the system. In the end, we verify the DNA double helix instability through induced torsional stress